Affordable Housing Units (Case study Gaza Strip) - Husam Qissi; Mojahed Mostafa; Rajai Awwad; Saed Allosh (My University, 2014)
Three alternative housing units were designed using timber, steel and shipping containers, in order to assess their characteristics ability to be converted, after applying proper modifications like thermal insulation, into residential units with convenient living conditions. Also, to determine the cost, lifetime and implementation time for each of them. Then to compare between them based on the cost, lifetime and implementation time.  Firstly, literature review was conducted to collect as much as possible of information about these three alternatives( steel, timber material and shipping containers) in order to evaluate their weak and strong points. Then, designing the three, approximately equal areas, suggested units based on the characteristics of each of them. The container house, steel house and timber house costs initially 101300, 92400 and 81200 Nis orderly. They took a construction period of 17,17 and 21 days orderly. The lifetime of each of them is 20, 30 and 15 years. The alternative with least cost after 60 years is steel house.